Deep crustal seismic reflection profiling : Australia 1978-2011 - Kennett, B. L. N. (Brian Leslie Norman), 1948-; Saygin, E.; Fomin, T.‏ ‎ (Tanya); Blewett, Richard (ANU Press, 2013)
"Deep Crustal Seismic Reflection Profiling : Australia 1978-2011" presents the full suite of reflection profiles penetrating the whole crust carried out in Australia from 1978-2011 by Geoscience Australia and partners. The set of reflection data comprises over 12,000 km of coverage across the whole continent, and provides an insight into the variations in crustal architecture in the varied geological domains. Each reflection profile is presented at approximately true scale with up to 220 km of profile per page and overlap between pages. Each reflection section is accompanied by a geological strip map showing the configuration of the line superimposed on 1:1M geology. The compilation includes a number of large scale reflection transects groups of 1,000 km or more that link across major geological provinces, and an extensive bibliography of reports and relevant publications. This atlas of reflection profiles penetrating the whole crust, with accompanying geological maps, represents a collaboration between the Research School of Earth Sciences at The Australian National University and Geoscience Australia. The reflection atlas project arose from work on the Australian Seismological Reference Model (AuSREM) sponsored by the National Infrastructure program of AuScope and the Australian National University.